Ferrimagnetic Tb–Fe Alloy Thin Films: Composition and Thickness Dependence of Magnetic Properties and All-Optical Switching - Hebler, Birgit; Hassdenteufel, Alexander; Reinhardt, Patrick; Karl, Helmut; Albrecht, Manfred (Frontiers in Materials, 2016)
Ferrimagnetic rare earth - transition metal Tb-Fe alloy thin films exhibit a variety of different magnetic properties, which depends strongly on composition and temperature. In this study, first the influence of the film thickness (5 - 85 nm) on the sample magnetic properties was investigated in a wide composition range between 15 at.% and 38 at.% of Tb. From our results, we find that the compensation point, remanent magnetization, and magnetic anisotropy of the Tb-Fe films depend not only on the composition but also on the thickness of the magnetic film up to a critical thickness of about 20-30 nm. Beyond this critical thickness, only slight changes in magnetic properties are observed. This behavior can be attributed to a growth-induced modification of the microstructure of the amorphous films, which affects the short range order. As a result, a more collinear alignment of the distributed magnetic moments of Tb along the out-of-plane direction with film thickness is obtained. This increasing contribution of the Tb sublattice magnetization to the total sample magnetization is equivalent to a sample becoming richer in Tb and can be referred to as an “effective” composition. Furthermore, the possibility of all-optical switching, where the magnetization orientation of Tb-Fe can be reversed solely by circularly polarized laser pulses, was analyzed for a broad range of compositions and film thicknesses and correlated to the underlying magnetic properties.